Pengaruh Profitabilitas, Leverage, Struktur Kepemilikan dan Ukuran Dewan Komisaris terhadap Pengungkapan Risiko Perusahaan (Business and Accounting Education Journal, 2022)
The study aim to analyze the effect of profitability, leverage, institusional ownership, public ownership and the size of the board of commissioners on corporate risk disclosure. y. This study used secondary data with the 51 population of non-bank financial service companies/institutions (LJNKB) listed on the Indonesia Stock Exchange in 2017- 2020. Samples selected based on purposive sampling method and acquired 43 company during four years. In this study using a descriptive analysis method with for hypothesis testing assisted by the SmartPLS version 3. The results of this research is the profitability and size of the board of commissioners have a positive affect on the risk disclosure. While, the leverage, institutional ownership and public ownership have no effect on risk disclosure.